Factor Activity Assays for Monitoring Extended Half-Life FVIII and Factor IX Replacement Therapies - Kitchen, Steve; Tiefenbacher, Stefan; Gosselin, Robert (Seminars in Thrombosis and Hemostasis, 2017)
The advent of modified factor VIII (FVIII) and factor IX (FIX) molecules with extended half-lives (EHLs) compared with native FVIII and FIX represents a major advance in the field of hemophilia care, with the potential to reduce the frequency of prophylactic injections and/or to increase the trough level prior to subsequent injections. Monitoring treatment through laboratory assays will be an important part of ensuring patient safety, including any tailoring of prophylaxis. Several approaches have been used to extend half-lives, including PEGylation, and fusion to albumin or immunoglobulin. Some of these modifications affect factor assays as routinely performed in hemophilia centers; so, laboratories will need to use FVIII and FIX assays which have been shown to be suitable on a product-by-product basis. For some products, there are marked differences between results obtained using one-stage or chromogenic assays and results obtained using different reagents in the one-stage assay. The laboratory should use an assay in which the recovery of the product closely aligns with the assay used by the pharmaceutical company to assign potency to the product, so that the units reported by the laboratory agree with those used to demonstrate efficacy of the product during clinical trials. Reported assay differences in relation to several of the EHL FVIII and FIX molecules will be reviewed in this article.
Keywords: Factor VIII assay; FIX assay; extended half-life FVIII; extended half-life FIX